Spinal dural fistula and anterior spinal artery supply from the same segmental artery: Case report of volumetric T2 MRI diagnosis and rational endovascular treatment - Shapiro, Maksim (Interv Neuroradiol, 2019)
Spinal dural fistulas (SDAVFs) occasionally arise from the same segmental artery as the radiculomedullary branch to the anterior spinal artery. In such cases, selective fistula embolization that does not endanger the anterior spinal artery is not possible, and surgical fistula disconnection is recommended. We present an exceptional case in which rational embolization strategy of SDAVF was feasible because of separate origins from a common segmental artery pedicle of the ventral radiculomedullary artery and the dorsal radicular artery branch supplying the fistula.